2019
DOI: 10.1590/0102-311x00086918
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances and daytime fatigue: data from the Brazilian National Health Survey, 2013

Abstract: This study aims to describe the prevalence of sleep disturbances and daytime fatigue and their association with socio-demographic and behavioral factors. Data from the Brazilian National Health Survey conducted in 2013 with 60,202 adults (≥ 18 years old) were used. The outcomes evaluated were self-reported sleep disturbances and daytime fatigue in the last two weeks. Sleep disturbance was defined as the presence of difficulty to fall asleep, frequently waking up during the night or sleeping more than usual; da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 33 publications
2
38
1
1
Order By: Relevance
“…Observing the results obtained in the psychomotor surveillance test (PC-PVT), it is observed that the higher the educational level, the better performance is achieved in all the parameters, which coincides with that indicated by Wendt et al [11]. Although it seems that there is a relationship between sleep duration and fatigue, this study is not conclusive to report this relationship, given that 44.8% of workers who declared fatigue did not have significant differences regarding the number of hours asleep when compared between groups sleeping less than 7 hours, between 7 and 8 hours or more than 8 hours.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Observing the results obtained in the psychomotor surveillance test (PC-PVT), it is observed that the higher the educational level, the better performance is achieved in all the parameters, which coincides with that indicated by Wendt et al [11]. Although it seems that there is a relationship between sleep duration and fatigue, this study is not conclusive to report this relationship, given that 44.8% of workers who declared fatigue did not have significant differences regarding the number of hours asleep when compared between groups sleeping less than 7 hours, between 7 and 8 hours or more than 8 hours.…”
Section: Discussionsupporting
confidence: 87%
“…Currently, the role of sleep has been relegated and the time spent sleeping has been decreasing over the years, as for many the sleep period is seen as a waste of time, even though we know that the consequences of poor sleep quality go beyond simple discomfort, affecting health conditions and life quality [10]. Sleep disturbances are also associated with increased risks of workplace accidents and car accidents due to daytime sleepiness as a result of bad night's sleep [11]. Sleep quality refers not only to the fact of sleeping well at night, but to have an adequate performance the following day.…”
Section: Sleep Qualitymentioning
confidence: 99%
“…Fatigue and psychiatric conditions including depression, anxiety, and post-traumatic stress disorder (PTSD) were reported to be associated with sleep disturbances (Germain et al 2017;Gould et al 2018;Steiger and Pawlowski 2019;Wendt et al 2019). We assessed fatigue, fatigue, anxiety, and PTSD to control the effect of those comorbidities on sleep disturbance.…”
Section: Variables For Analysismentioning
confidence: 99%
“…Sleep quality and disorders (e.g, insomnia and sleep apnea) are associated with an increased risk of all-cause mortality, mental health problems, obesity, learning and memory problems, and chronic diseases. Sleep disturbances are also associated with increased risks of workplace accidents and car accidents due to daytime sleepiness as a result of a bad night's sleep (Wendt et al 2019).…”
Section: Sleep Qualitymentioning
confidence: 99%